2021
DOI: 10.1021/acs.nanolett.1c03604
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Electron Transport and Ortho–Para Fluctuation of Water Molecule in H2O@C60 Single Molecule Transistors

Abstract: Light molecules such as H 2 O are the systems in which we can have access to quantum mechanical information on their constituent atoms. Here, we have investigated electron transport through H 2 O@C 60 single molecule transistors (SMTs). The H 2 O@C 60 SMTs exhibit Coulomb stability diagrams that show multiple tunneling-induced excited states below 30 meV. Furthermore, we have performed terahertz (THz) photocurrent spectroscopy on H 2 O@C 60 SMTs and confirmed the same excitations. From comparison between exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(81 reference statements)
1
6
0
Order By: Relevance
“…In this study, a fullerene derivative of CPTA was used as the conductive channel material. Simple fullerenes such as C 60 and C 70 and variable endohedral fullerenes have been employed as single-molecule or film , devices. In comparison with these fullerenes, CPTA has advantages such as oversolvability in solution and uniform adhesion on the substrate surface .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a fullerene derivative of CPTA was used as the conductive channel material. Simple fullerenes such as C 60 and C 70 and variable endohedral fullerenes have been employed as single-molecule or film , devices. In comparison with these fullerenes, CPTA has advantages such as oversolvability in solution and uniform adhesion on the substrate surface .…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Furthermore, the ortho-para fluctuations have also been demonstrated in H 2 O@C 60 SMTs. [35] The fluctuation between ortho-and parawater states has been demonstrated on timescales shorter than 1 min. [35] However, in another single-molecule junction study of H 2 O@C 60 , it was found that H 2 O is electrostatically isolated.…”
Section: Introductionmentioning
confidence: 97%
“…[35] The fluctuation between ortho-and parawater states has been demonstrated on timescales shorter than 1 min. [35] However, in another single-molecule junction study of H 2 O@C 60 , it was found that H 2 O is electrostatically isolated. [36] In this work, we fabricated SMTs based on H 2 O@C 60 molecules.…”
Section: Introductionmentioning
confidence: 97%
“…[8e] Different responses of ortho and para spin isomers of water inside C 60 to external EFs were observed by Meier et al, who suggested a partial shielding explanation based on the analysis of the experimentally measured dipole moment. [12] Delaney and Greer calculated the overall EF inside C 60 and found that only 25% of the external EF imposed can penetrate into the cage, and create a spherical region (of radius 2 Å) with a constant field around the centroid of C 60 . [8a] They also employed different basis sets and found that the magnitude of EF penetration was barely changed.…”
Section: Introductionmentioning
confidence: 99%
“…The shielding effect of C 60 was illuminated in a combined experimental and theoretical study by Jarivs et al ., who found that the STM, non‐contact atomic force microscopy (ncAFM) and valence band X‐ray photoemission spectroscopy (VB‐XPS) cannot distinguish between empty C 60 and the ones filled with H 2 O, from the perspectives of orbitals, stiffness and the dielectric properties [8e] . Different responses of ortho and para spin isomers of water inside C 60 to external EFs were observed by Meier et al ., who suggested a partial shielding explanation based on the analysis of the experimentally measured dipole moment [12] . Delaney and Greer calculated the overall EF inside C 60 and found that only 25% of the external EF imposed can penetrate into the cage, and create a spherical region (of radius 2 Å) with a constant field around the centroid of C 60 [8a] .…”
Section: Introductionmentioning
confidence: 99%